Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A Dominant Founder Lineage Has Possible Fitness Costs for the Endangered Mexican Grey Wolf - Yeraldi Loera; Manisha Khakoo; Emily Krueckeberg; Ingrid G. Nilsson; Zehao Wu; Maggie Dwire; Jennifer Adams; Lisette Waits; John K. Oakleaf; Mariel L. Campbell; Jonathan L. Dunnum; Joseph A. Cook; et al. (Molecular Ecology, 2026)
The Mexican grey wolf ( Canis lupus baileyi ) is an endangered and genetically distinct subspecies of grey wolf adapted to the warm climates of the southwestern United States and Mexico. Following centuries of eradication efforts, Mexican grey wolves were protected under the Endangered Species Act in 1976, prompting an international ex situ breeding program to preserve their genetic legacy. Seven remnant wolves founded the three distinct lineages of this program: McBride, Ghost Ranch, and Aragón. However, concerns of rising inbreeding levels motivated the implementation of inter‐lineage pairings to decelerate genetic erosion. To evaluate the genetic health of the ex situ managed population, we analysed genome‐wide variation across several generations of breeding wolves and their descendants ( n = 179). Despite ongoing conservation interventions, we found a sharp decline in effective population size over the past 50 generations. However, estimates of inbreeding diminished over time following the inter‐lineage pairings, reflecting efficient pedigree management or potential fitness costs of inbreeding depression, as higher levels of inbreeding and autozygosity were associated with reduced lifespan and reproductive performance. Increasing contributions of Ghost Ranch and Aragón ancestry also aided in reducing levels of inbreeding observed in the more genetically distinct McBride lineage. These findings highlight the challenges of maintaining genetic diversity in bottlenecked populations, reveal fine‐scale patterns of inbreeding within the pedigree and underscore the urgent need to preserve genetic contributions from all founder lineages. Genomic insights from this study can guide breeding strategies to reduce kinship, balance ancestry and mitigate inbreeding depression, safeguarding the evolutionary legacy and the long‐term persistence of the Mexican grey wolf.

Dissimilatory nitrate reduction to ammonium driven by iron tolerant Lutibacter in coastal sediments - Maha Alharbi; Thanh Nguyen-Dinh; Wei Wen Wong; Pok Man Leung; Adam J. Kessler; Chris Greening; Perran L.M. Cook (Science of The Total Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Fact-based environmental messaging did not influence Australians' attitudes and intentions towards cultivated seafood - Sarah J. Cook; Adam P.A. Cardilini; Alexa Hayley; Prue Francis (Food Quality and Preference, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Catalytic consequences of catalyst pellet architecture on the direct production of dimethoxymethane from methanol. - Sebastian M.K. Cook; William Thomas Broomhead; Adam Johnston; Ya-Huei Cathy Chin; José E. Herrera (Chemical Engineering Journal, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A synthetic analysis of post-construction displacement and attraction of marine birds at offshore wind energy installations - Juliet Lamb; Julia Gulka; Evan Adams; Aonghais Cook; Kathryn A. Williams (Environmental Impact Assessment Review, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Pulses of labile carbon cause transient decoupling of fermentation and respiration in permeable sediments - Philipp A. Nauer; Adam J. Kessler; Puspitaningsih Hall; Maria Elena Popa; Sophie ten Hietbrink; Tess Hutchinson; Wei Wen Wong; Karl Attard; Ronnie N. Glud; Chris Greening; Perran L. M. Cook (Limnology and Oceanography, 2023)
Dihydrogen (H 2 ) is an important intermediate in anaerobic microbial processes, and concentrations are tightly controlled by thermodynamic limits of consumption and production. However, recent studies reported unusual H 2 accumulation in permeable marine sediments under anoxic conditions, suggesting decoupling of fermentation and sulfate reduction, the dominant respiratory process in anoxic permeable marine sediments. Yet, the extent, prevalence and potential triggers for such H 2 accumulation and decoupling remain unknown. We surveyed H 2 concentrations in situ at different settings of permeable sand and found that H 2 accumulation was only observed during a coral spawning event on the Great Barrier Reef. A flume experiment with organic matter addition to the water column showed a rapid accumulation of hydrogen within the sediment. Laboratory experiments were used to explore the effect of oxygen exposure, physical disturbance and organic matter inputs on H 2 accumulation. Oxygen exposure had little effect on H 2 accumulation in permeable sediments suggesting both fermenters and sulfate reducers survive and rapidly resume activity after exposure to oxygen. Mild physical disturbance mimicking sediment resuspension had little effect on H 2 accumulation; however, vigorous shaking led to a transient accumulation of H 2 and release of dissolved organic carbon suggesting mechanical disturbance and cell destruction led to organic matter release and transient decoupling of fermenters and sulfate reducers. In summary, the highly dynamic nature of permeable sediments and its microbial community allows for rapid but transient decoupling of fermentation and respiration after a C pulse, leading to high H 2 levels in the sediment.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

Engineering, Ecological and Social Monitoring of the Largest Underwater Sculpture in the World at John Brewer Reef, Australia - Adam Smith; Al Jayson Songcuan; Nathan Cook; Rachelle Brown; Kailash Cook; Reuben Richardson (Journal of Marine Science and Engineering, 2022)
The largest underwater sculpture in the world, the ‘Coral Greenhouse’ by artist Jason deCaires Taylor, was commissioned by the Museum of Underwater Art and installed at John Brewer Reef, Australia, in December 2019. The planning process required certified engineering design drawings associated with design life, durability and suitability of materials, and baseline ecological surveys. Following approval, the operational phase required annual monitoring of substrate, ecology, social values, and marine debris. We geo-referenced three permanent transects and designed a before/after rapid monitoring assessment of substrate, fish, and invertebrates. Substrate surveys indicated 11% concrete and 89% sand. Fish surveys indicated significant increases of diversity and abundance, with 12 species and 65 individuals recorded in 2018 compared to 46 species and 365 individuals recorded in 2022. Macroinvertebrate species maintained no significant trends in abundance, species richness, and diversity with respect to time between 2018 and 2022. We monitored coral restoration and natural recruitment at the site, measuring aesthetics, survivorship of planted corals, and coral recruitment. Of 131 corals transplanted in March 2020, survivorship was 100% at 1 month, 92% at 6 months, and 91.6% at 12 months. Hard and soft corals were recruited to the structure at a density of 8.35 hard corals/m2 and 10.9 soft corals/m2 over 26 months.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Prostate cancer addiction to oxidative stress defines sensitivity to anti-tumor neutrophils - Diane L. Costanzo-Garvey; Adam J. Case; Gabrielle F. Watson; Massar Alsamraae; Arpita Chatterjee; Rebecca E. Oberley-Deegan; Samikshan Dutta; Maher Y. Abdalla; Tammy Kielian; Merry L. Lindsey; Leah M. Cook (Clinical & Experimental Metastasis, 2022)
Bone metastatic prostate cancer (BM-PCa) remains one of the most difficult cancers to treat due to the complex interactions of cancer and stromal cells. We previously showed that bone marrow neutrophils elicit an anti-tumor immune response against BM-PCa. Further, we demonstrated that BM-PCa induces neutrophil oxidative burst, which has previously been identified to promote primary tumor growth of other cancers, and a goal of this study was to define the importance of neutrophil oxidative burst in BM-PCa. To do this, we first examined the impact of depletion of reactive oxygen species (ROS), via systemic deletion of the main source of ROS in phagocytes, NADPH oxidase (Nox)2, which we found to suppress prostate tumor growth in bone. Further, using pharmacologic ROS inhibitors and Nox2-null neutrophils, we found that ROS depletion specifically suppresses growth of androgen-insensitive prostate cancer cells. Upon closer examination using bulk RNA sequencing analysis, we identified that metastatic prostate cancer induces neutrophil transcriptomic changes that activates pathways associated with response to oxidative stress. In tandem, prostate cancer cells resist neutrophil anti-tumor response via extracellular (i.e., regulation of neutrophils) and intracellular alterations of glutathione synthesis, the most potent cellular antioxidant. These findings demonstrate that BM-PCa thrive under oxidative stress conditions and such that regulation of ROS and glutathione programming could be leveraged for targeting of BM-PCa progression.

Recovery of denitrification and dissimilatory nitrate reduction to ammonium following reoxygenation of sediments from a periodically hypoxic temperate lagoon - Keryn L. Roberts; Wei Wen Wong; Jeff Shimeta; Adam J. Kessler; Perran L. M. Cook (Limnology and Oceanography, 2022)
Eutrophication and stratification events have increased the incidences of hypoxia and anoxia in coastal environments. The depletion of oxygen in these environments can lead to a shift in biogeochemical processes such as denitrification and dissimilatory nitrate reduction to ammonium (DNRA). The balance between denitrification and DNRA is critical because denitrification leads to a loss of bioavailable nitrogen and DNRA maintains it within the system. This study examined the effects of reoxygenation on denitrification and DNRA in sediments collected from a periodically hypoxic system (Gippsland Lakes, Australia) and subjected to experimental hypoxia using a modified 15 N‐isotope pairing technique. For freshly collected sediments, the ratio of denitrification : DNRA was generally 1. Profiles of 15 N‐N 2 and accumulation in these experiments showed denitrification and DNRA generally only took place in the surface ~ 2 cm of sediment. Prolonged experiments with reoxygenated sediments showed a decrease in the denitrification : DNRA to

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Influence of the Toxin-Producing Dinoflagellate, Alexandrium catenella (1119/27), on the Survival and Reproduction of the Marine Copepod, Acartia tonsa, During Prolonged Exposure - Ali H. Abdulhussain; Kathryn B. Cook; Andrew D. Turner; Adam M. Lewis; Thomas S. Bibby; Daniel J. Mayor (Frontiers in Marine Science, 2021)
Copepods can feed on, and may regulate, the blooms of harmful algae (HA), and may also facilitate dinoflagellate blooms by inducing toxin production and through selective grazing. However, exposure to HA may also cause mortality and reproductive impairment in copepods, with detrimental effects at the population-scale. Here we present the toxin profile of the dinoflagellate, Alexandrium catenella (formerly Alexandrium tamarense ), and examine how it affects the survival and reproduction of the cosmopolitan marine copepod, Acartia tonsa . Healthy adult copepods were exposed to mono-specific diets of toxic and non-toxic strains of A. catenella (1119/27 and 1119/19, respectively) and non-toxic Rhodomonas sp. for 10 days alongside unfed controls to examine how their survival was influenced by likely HA bloom conditions. Additional 2-day experiments examined how their egg production rate and hatching success were affected by food deprivation, toxic A. catenella , a non-toxic alternative and a mixture of toxic and non-toxic prey, at high and low concentrations. Survival of A. tonsa declined over the 10-day experiment in all treatments but was not significantly lower in the toxic A. catenella treatment; mortality was only significantly enhanced in the unfed animals, which showed 100% mortality after 9 days. Egg production rates and hatching success from females in the unfed and toxic A. catenella treatments were all significantly lower than values observed in females fed Rhodomonas sp. or non-toxic A. catenella . Animals offered 1,000 μg C L –1 of Rhodomonas sp. and a 50:50 mixture of toxic A. catenella and Rhodomonas sp. produced significantly more eggs than animals fed toxic A. catenella alone. These results were not apparent at prey concentrations of 100 μg C L –1 . The percentages of eggs to successfully hatch from females offered mono-specific diets of toxic A. catenella were always close to zero. Collectively, our results indicate that adult female A. tonsa can acquire sufficient energy from toxic A. catenella to survive, but suffer reproductive impairment when feeding on this prey alone.

Immersion challenge of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. did not increase the severity of Neoparamoeba perurans ‐induced amoebic gill disease (AGD) - Chloe J. English; Natasha A. Botwright; Mark B. Adams; Andrew C. Barnes; James W. Wynne; Paula C. Lima; Mathew T. Cook (Journal of Fish Diseases, 2021)
Amoebic gill disease (AGD) is one of the main health issues impacting farmed Atlantic salmon. Neoparamoeba perurans causes AGD; however, a diversity of other amoeba species colonizes the gills and there is little understanding of whether they are commensal or potentially involved in different stages of gill disease development. Here, we conduct in vivo challenges of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. to investigate their pathogenicity to Atlantic salmon gills. Additionally, we assessed whether the presence of Nolandella sp. and Pseudoparamoeba sp. influences the onset and/or severity of N. perurans ‐induced AGD. All three strains attached and multiplied on the gills according to qPCR analysis. Furthermore, minor gross gill lesions and histological changes were observed post‐exposure. While N. perurans was found associated with classical AGD lesions, Nolandella sp. and Pseudoparamoeba sp. were not found associated with lesion sites and these lesions did not meet the expected composite of histopathological changes for AGD. Moreover, the presence of these non‐ N. perurans species did not significantly increase the severity of AGD. This trial provides evidence that cultured Nolandella sp. and Pseudoparamoeba sp. do not induce AGD and do not influence the severity of AGD during the early stages of development.

Spiraling Down Hillslopes: Nutrient Uptake from Water Tracks in a Warming Arctic - Tamara K. Harms; Christopher L. Cook; Adam N. Wlostowski; Michael N. Gooseff; Sarah E. Godsey (Ecosystems, 2019)

Climate Change Vulnerability of American Lobster Fishing Communities in Atlantic Canada - Blair J. W. Greenan; Nancy L. Shackell; Kiyomi Ferguson; Philip Greyson; Andrew Cogswell; David Brickman; Zeliang Wang; Adam Cook; Catherine E. Brennan; Vincent S. Saba (Frontiers in Marine Science, 2019)

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

Cable bacteria promote DNRA through iron sulfide dissolution - Adam J. Kessler; Michaela Wawryk; Ugo Marzocchi; Keryn L. Roberts; Wei Wen Wong; Nils Risgaard‐Petersen; Filip J. R. Meysman; Ronnie N. Glud; Perran L. M. Cook (Limnology and Oceanography, 2019)
Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half‐reactions of their sulfide‐oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3) by indirectly affecting denitrification and/or DNRA by changing the Fe 2+ concentration in the surrounding sediment. We performed 15 N labeling laboratory experiments to measure these three processes using cable bacteria containing sediments from the Yarra River, Australia, and from Vilhelmsborg Sø, Denmark. Our results revealed that in the targeted systems, cable bacteria themselves did not perform significant rates of denitrification, DNRA, or nitrification. However, cable bacteria exhibited an important indirect effect, whereby they increased the Fe 2+ pool through iron sulfide dissolution. This elevated availability of Fe 2+ significantly increased DNRA and in some cases decreased denitrification. Thus, cable bacteria presence may affect the relative importance of DNRA in sediments and thus the extent by which bioavailable nitrogen is lost from the system.

Response of Scotian Shelf silver hake ( Merluccius bilinearis ) to environmental variability - Daniel Reed; Stéphane Plourde; Adam Cook; Pierre Pepin; Benoit Casault; Caroline Lehoux; Catherine Johnson (Fisheries Oceanography, 2019)
Commercially‐exploited fish populations are not only shaped by fishing pressure, but also by the dynamics of their environment. By quantifying the influence of environmental variability, fisheries management advice can be improved and uncertainties reduced. To this end, we developed statistical models of the response of Scotian Shelf silver hake stock metrics to variability in zooplankton community composition and phenology over the past 18 years and in the physical environment since 1985. Dominant modes of variability in these pelagic habitat indicators were characterized using principal component analysis, and the relationships of silver hake condition, abundance, and recruitment to pelagic habitat variability were assessed using generalized additive models. Condition was largely modulated by the onset and duration of the spring bloom, which controls food availability. In contrast, adult abundance was governed by composition of the zooplankton community and bottom‐water temperature, which dictates the distribution of silver hake. Finally, recruitment was affected by both thermal conditions and food availability. Our results presented here form the basis for qualitative assessment of ecosystem attributes and the influence on silver hake stock productivity.

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Buffel grass and climate change: a framework for projecting invasive species distributions when data are scarce - Tara G. Martin; Helen Murphy; Adam Liedloff; Colette Thomas; Iadine Chadès; Garry Cook; Rod Fensham; John McIvor; Rieks D. van Klinken (Biological Invasions, 2015)

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses - Coleen C. Suckling; Melody S. Clark; Christine Beveridge; Lars Brunner; Adam D. Hughes; Elizabeth M. Harper; Elizabeth J. Cook; Andrew J. Davies; Lloyd S. Peck (Invertebrate Reproduction & Development, 2014)

Quantifying denitrification in rippled permeable sands through combined flume experiments and modeling - Adam J. Kessler; Ronnie N. Glud; M. Bayani Cardenas; Morten Larsen; Michael F. Bourke; Perran L. M. Cook (Limnology and Oceanography, 2012)
We measured denitrification in permeable sediments in a sealed flume tank with environmentally representative fluid flow and solute transport behavior using novel measurements. Numerical flow and reactive transport models representing the flume experiments were implemented to provide mechanistic insight into the coupled hydrodynamic and biogeochemical processes. There was broad agreement between the model results and experimental data. The model showed that the coupling between nitrification and denitrification was relatively weak in comparison to that in cohesive sediments. This was due to the direct advective transport between anoxic pore water and the overlying water column, and little interaction between the mostly oxic advective region and the underlying anoxic region. Denitrification was therefore mainly fueled by nitrate supplied from the water column. This suggests that the capacity of permeable sediments with nonmigratory ripples to remove bioavailable nitrogen from coastal ecosystems is lower than that of cohesive sediments. We conclude that while experimental measurements provide a good starting point for constraining key parameters, reactive transport models with realistic kinetic and transport parameters provide critical insight into biogeochemical processes in permeable sediment that are difficult to experimentally evaluate.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Managing Uncertainty in Site-Specific Management: What is the Best Model? - Matthew L. Adams; Simon Cook; Robert Corner (Precision Agriculture, 2000)

Seasonal soil‐surface carbon fluxes from the root systems of young Pinus radiata trees growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; Freeman J. Cook; David Whitehead; John A. Adams (Global Change Biology, 2000)
Summary Elevated atmospheric CO 2 concentration may result in increased below‐ground carbon allocation by trees, thereby altering soil carbon cycling. Seasonal estimates of soil surface carbon flux were made to determine whether carbon losses from Pinus radiata trees growing at elevated CO 2 concentration were higher than those at ambient CO 2 concentration, and whether this was related to increased fine root growth. Monthly soil surface carbon flux density ( f ) measurements were made on plots with trees growing at ambient (350) and elevated (650 μmol mol −1 ) CO 2 concentration in large open‐top chambers. Prior to planting the soil carbon concentration (0.1%) and f (0.28 μmol m −2 s −1 at 15 °C) were low. A function describing the radial pattern of f with distance from tree stems was used to estimate the annual carbon flux from tree plots. Seasonal estimates of fine root production were made from minirhizotrons and the radial distribution of roots compared with radial measurements of f . A one‐dimensional gas diffusion model was used to estimate f from soil CO 2 concentrations at four depths. For the second year of growth, the annual carbon flux from the plots was 1671 g y −1 and 1895 g y −1 at ambient and elevated CO 2 concentrations, respectively, although this was not a significant difference. Higher f at elevated CO 2 concentration was largely explained by increased fine root biomass. Fine root biomass and stem production were both positively related to f. Both root length density and f declined exponentially with distance from the stem, and had similar length scales. Diurnal changes in f were largely explained by changes in soil temperature at a depth of 0.05 m. Ignoring the change of f with increasing distance from tree stems when scaling to a unit ground area basis from measurements with individual trees could result in under‐ or overestimates of soil‐surface carbon fluxes, especially in young stands when fine roots are unevenly distributed.

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.